FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING SEBAGAI VARIABEL DEPENDEN PADA SEKTOR PERINDUSTRIAN - Henlindra , Catherine Oktovella; Santioso, Linda (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The main objective of this study is to analyze the effect of leverage, firm size, net working capital, and growth opportunity on cash holding in industrial sector companies listed on the Indonesia Stock Exchange in 2019–2021. This study uses a purposive sampling technique with the number of companies obtained as many as 38 companies that are included in the purposive sampling criteria. The data used are secondary data from the company's annual report obtained through the Indonesia Stock Exchange website and the company's official website. Data processing uses the E-Views 12 application program with a quantitative method. The results of this study indicate that the independent variables leverage, firm size, & growth opportunity have no effect on the dependent variable cash holding, and net working capital has a positive effect on cash holding.